High School EFL Teachers’ Continuous Professional Development: Target Needs, Reflection and Challenges - Mulualem Eshete Mekie; Girma Gezahegn (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Purpose - This research investigated the high school EFL teachers’ continuous professional development target needs, reflection, and challenges. Further, the target needs of the EFL teachers were analyzed by adapting Hutchinson and Waters’ model (1987). Design/methodology/approach - The data were collected using a test, questionnaire (consisted of five parts), and interview; these were administered to 20 high school EFL teachers. A test was administered to identify EFL teachers' present situation and difficulties, and questionnaire parts 1, 2 and 4 dealt with the EFL teachers' difficulties, needs and purposes in the program. Findings/result - the result revealed that high school EFL teachers face various challenges in the current program they are taking. Originality/value - the professional development should be revised according to EFL teachers’ target needs, reflections, and challenges. Paper type - Research paper